2022
DOI: 10.53730/ijhs.v6n2.8971
|View full text |Cite
|
Sign up to set email alerts
|

effectiveness of animated videos to improve science process skills and creativity in science learning during COVID-19 pandemic

Abstract: The main objective of this research was to determine the effectiveness level of using animated videos in science learning to improve students’ science process skills and creativity during COVID-19 Pandemic. The research approach used was development research. The subjects involved in the effectiveness test of animated videos were 60 students from the fifth grade of SD Negeri 4 Pringgabaya. The instruments used to obtain data on the effectiveness test results of utilization of animated videos in science learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…Furthermore, COVID19 is rapidly spreading, is humanto-human transmissible, specifically in health care settings, and can lead to death. Therefore, midwives' emotional and behavioral reactions must be recognized and empowered through specialized education and training to overcome psychological distress and help midwives provide care under extremely challenging clinical conditions such as the spread of the novel coronavirus (Alnazly et al, 2021;Nurhayati et al, 2022). In the current study, half of the midwives' participants indicated higher levels of burnout.…”
Section: Association Of the Scale Scores Of The Participants With The...mentioning
confidence: 75%
“…Furthermore, COVID19 is rapidly spreading, is humanto-human transmissible, specifically in health care settings, and can lead to death. Therefore, midwives' emotional and behavioral reactions must be recognized and empowered through specialized education and training to overcome psychological distress and help midwives provide care under extremely challenging clinical conditions such as the spread of the novel coronavirus (Alnazly et al, 2021;Nurhayati et al, 2022). In the current study, half of the midwives' participants indicated higher levels of burnout.…”
Section: Association Of the Scale Scores Of The Participants With The...mentioning
confidence: 75%
“…Fun in learning, interest in learning time, social implications, scientific normality for science learning (Sulistioning et al, 2020), & outdoor learning (Skarstein & Ugelstad, 2020) Learning should not only be in classroom 8 Necessity of media literacy (Anwar et al, 2020) that is embodied in the form of science learning framework online (Opere, 2021), online community (Herodotou et al, 2022), flipped classroom (Shana & Alwaely, 2021), open educational resources (Gerard et al, 2022), use of multimedia (Herianto & Wilujeng, 2021), virtual reality understanding (Hite, 2022), virtual science learning (Telenius et al, 2020), using Edmodo (Ryane & El Faddouli, 2020), animated videos (Nurhayati et al, 2022), motion graphic animation videos (Hanif, 2020), mobile science learning (Chang et al, 2021;Jeno et al, 2020)., VR simulations (Pande et al, 2021) Science learning media must be technologically advanced 9 10 Urgency of cognitive assessment techniques (Darmawan et al, 2020), multiple self-regulated learning measures (Gandomkar et al, 2020), & performance assessment (Yakob et al, 2021).…”
Section: Science Learning Needsmentioning
confidence: 99%
“…TPACK is the best approach for a teacher in a pandemic era because a lack of awareness of technology will hamper the transmission of knowledge from teachers to learners (Nurhayati et al, 2020). The TPACK approach incorporates teacher-student interactions, teaching-learning processes and technology-enhanced systems to uphold shared and active learning, knowledge and resource sharing, and resourceful communication (Akram et al, 2021).…”
Section: Technological Pedagogical Content Knowledge (Tpack)mentioning
confidence: 99%